James Bond a dylematy tożsamościowe Brytyjczyków – kultura popularna a kształtowanie tożsamości narodowej - Hejwosz-Gromkowska, Daria (Studia Edukacyjne, 2020)
The author assumes that popular culture plays a powerful role in the process of socialization of young generation. The author tries to present that the conventional national symbols are being replaced by pop symbols and thus become the sources of national identity. The concepts of banal nationalism put forward by Michael Billig or Tim Enderson’s idea of everyday life’s practices in the development of national identity are being used. In the text, the phenomenon of James Bond is used to analyze the contemporary debates on British identity (Britishness). The author assumes that James Bond is a great example of Englishness that serves as a complex manifestation of a British hero which may, in turn, play a crucial role in political, civic, and patriotic education.